Analysis of the Threat of Social Conflict on The Arrival of the Rohingya Ethnicity in The Aceh Province Region - Hilmansyah, Hilmansyah (Security Intelligence Terrorism Journal (SITJ), 2025)
The arrival of the Rohingya ethnic group in the Aceh Province region received a reaction of rejection from the local Aceh community. Changes in the perception of local Acehnese people regarding the existence of Rohingya refugees have led to various demonstrations of rejection and expulsion of refugees from temporary shelters. The increasing wave of refugee arrivals landing in various areas of Aceh has had an impact on the escalation of social conflict between the local Acehnese community and the Rohingya ethnic group. This research examines the causes of social conflict, analysis of the threat of social conflict, and intelligence strategies in resolving social conflicts that occur between the local Acehnese community and the Rohingya ethnic group. The theories used in this research are conflict theory, threats, intelligence strategy, and Friedrich Glasl's conflict escalation model. The research method uses descriptive qualitative with collection techniques in the form of observation, interviews and literature study. The results of the research show that the causes of social conflict are the struggle for resources, conflicting values, and other factors including the effects of social media, indefinite handling time and budget, as well as the escalation of refugee arrivals. Threat analysis shows that the arrival of the Rohingya ethnic group is a threat to conflict because it fulfills the variables of ability, intention and opportunity. In this case, to overcome this threat, it is necessary to carry out an intelligence strategy including the implementation of Presidential Decree 125 of 2016 concerning Handling Refugess from Abroad, synergy and coordination, as well as diplomacy (means), carrying out relocation, economic empowerment and strengthening maritime security (ways), in the context of recognizing citizenship, minimizing social conflict, and cross-cultural understanding (ends).